Volatile Composition, Sensory Profile, and Consumers’ Acceptance of Fondillón - Hanán Issa-Issa; Luis Noguera-Artiaga; Esther Sendra; Antonio J. Pérez-López; Francisco Burló; Ángel A. Carbonell-Barrachina; David López-Lluch (Journal of Food Quality)
No scientific information exists on quality attributes of Fondillón, a special naturally sweet wine produced from overripe Monastrell grapes and one of the only six wines that can use its own name according to European Union Regulations. The aim of this study was to analyze the composition (physicochemical and volatile profile) and sensory quality of this special wine. A specific lexicon to describe wines under the Alicante PDO was developed, using 28 attributes (11 flavor notes, 3 visual, 2 global, and 12 defects). Forty volatile compounds were isolated, and esters were the main chemical family of volatile compounds of Fondillón (∼70%), followed by alcohols (∼20%). Furthermore, two volatile compounds (TDN and vitispirane) were positively correlated with the age of the Fondillón samples, under the specific working conditions used in this study. According to a sensory study, this wine was appreciated by Spanish consumers as having intense fruity notes, high alcohol content, and some bitter and balsamic notes; however, further research is needed to identify the proper profile of Fondillón consumers and their buying and acceptance drivers.